PERAN MANAJEMEN DALAM BIMBINGAN PENYULUHAN ISLAM - Hamdi Abdul Karim (INSTITUT AGAMA ISLAM NEGERI METRO, 2019)
Islamic guidance counseling management discusses how management is carried out by extension agents in carrying out their duties, including preparing education activities starting from determining the schedule and location of activities, organizing carried out by extension agents, of course, with the job description set up until the extension activities and stages evaluation to see the extent to which the success of the program activities that have been carried out with the aim of repairs. Planning in Islamic Counseling Guidance is the selection or determination of organizational goals in this case Counseling in Offices and certain institutions to determine strategies, policies, projects, programs, procedures, methods, systems, budgets and standards needed to achieve goals . In planning is also a plan or plan of activities that will be carried out within a certain period of time. The design or plan of the activity is arranged in a systematic, organized, and coordinated manner over a period of time, so that the implementation of extension activities goes well.